Implementing Listen, Repeat, and Trace (LRT) Technique to Improve Students’ English Vocabularies. - Wulan, Retno; Nurlaili (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This research explored the effectiveness of the Listen, Repeat, and Trace technique in enhancing students' English vocabularies. Employing the Collaborative Classroom Action Research, the researchers conducted this study in two cycles using pre- and post-tests to assess students’ vocabularies enhancement. Each cycle consisted of planning, action, observation, and reflection stages to investigate all 31 students at the eighth grade of one high school in Jambi Province, Indonesia. The results revealed a significant improvement of learners’ English vocabularies after they received the LRT treatment technique. Moreover, the average score from both post-test in cycle 1 and cycle 2 significantly increased. The mean score of cycle 1 was 74.36 (14 students or 46% who passed Minimum Mastery Criterion), while in cycle 2 was 85.32 (25 students or 81 % who passed Minimum Mastery Criterion). This technique offered a pedagogical approach that goes beyond traditional rote memorization methods, providing students with a dynamic and engaging learning experience. Ultimately, the LRT technique promoted a positive learning environment by fostering student engagement and motivation. The interactive nature of the technique encouraged active participation and collaboration among students leading to better language learning experience. Thus, the educators are expected to implement the LRT technique as an innovative strategy to promote vocabulary development and enrich language learning outcomes.